Active impacts on warm fogs and instrumental determination of their efficiency - K. M. Kalov; R. K. Kalov (Наука. Инновации. Технологии, 2022)
Introduction: Despite the presence of a large number of theoretical and experimental works of Russian and foreign authors (for example [1-3]), the problem of scattering of warm fogs and low layered clouds (LLC) remains unresolved to the present time. Of the variety of warm fog scattering methods proposed to date, only thermal ones are the closest to achieving the expected result. Not fully solved the problem of the instrumental determination of the horizontal and vertical extents of the zone illuminated by artificial dissipation of fog and LLC. Materials and methods of research: In this paper, a thermal method of methods of scattering of warm fogs and LLC, based on the use of high-temperature sources of thermal energy. The sources used were explosions of thermal charges, which increased the temperature and pressure in the fog and LLC. This rise leads to the evaporation of the mist in the treated area. Developed laser radar device to measure the physical ef-iciency of the artiicial dissipation of warm fog and LLC. The device is used in stationary conditions on the ground and on Board the Yak-40 laboratory aircraft. Results of the study and their Discussion: Under the thermal method of fog and LLC scattering, droplets crossing the shock wave front are crushed into smaller droplets and evaporate under the action of increasing pressure and temperature during the explosion in a cloud medium. The formulas for calculating the excess pressure and temperature in the fog during the explosion of thermal charges, the time of complete evaporation of droplets and the radius of the zone of enlightenment in the fog are obtained. Calculations have shown that the excess pressure and temperature in the fog in the explosion of heat charge increase with increasing charge. The temperature at the front of the shock wave is still noticeably higher than the temperature of the undisturbed air at distances up to 200 meters from the explosion site. If the explosion of heat charge occurs at a low altitude (1... 2 m) above the ground, the complete evaporation of fog drops is observed in a radius of 800 m and more. Conclusions. The thermal method developed by us makes it possible to create zones of enlightenment by small explosions of a thermal charge under the influence of temperature and pressure increase on a compression wave in comparison with their values in the unperturbed air. When a small charge explodes, a cloud of expanding explosive gases appears, the thermal radiation of which evaporates droplets of cloud formation and creates a zone of enlightenment in the fog up to 800 m. the Laser-locating device with a laser emitter IZ-25-1 at a wavelength of 0.532 pirn with high accuracy (4...5 m) determines the boundaries of the fog scattering zone.